2021
DOI: 10.3389/fnhum.2020.617187
|View full text |Cite
|
Sign up to set email alerts
|

Windows of Integration Hypothesis Revisited

Abstract: In the ongoing research of the functions of consciousness, special emphasis has been put on integration of information: the ability to combine different signals into a coherent, unified one. Several theories of consciousness hold that this ability depends on – or at least goes hand in hand with – conscious processing. Yet some empirical findings have suggested otherwise, claiming that integration of information could take place even without awareness. Trying to reconcile this apparent contradiction, the “windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Recently, based on a large amount of evidence of unconscious processing (Bruno et al, 2020;Chen et al, 2020;Eriksson et al, 2020;Soto et al, 2019), it has been found that multiple subliminal stimuli can integrate with each other. This nding greatly advanced the understanding of unconscious information processing and integration (Hirschhorn et al, 2021;Tu et al, 2020;Van Opstal, 2021;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Recently, based on a large amount of evidence of unconscious processing (Bruno et al, 2020;Chen et al, 2020;Eriksson et al, 2020;Soto et al, 2019), it has been found that multiple subliminal stimuli can integrate with each other. This nding greatly advanced the understanding of unconscious information processing and integration (Hirschhorn et al, 2021;Tu et al, 2020;Van Opstal, 2021;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…According to an opposing dominant view, however, it is contextually inconsistent stimuli that actually benefit from increased access to awareness and therefore may exert influence on performance earlier than consistent stimuli when presented unconsciously [80] (see also [81,82]). These findings, though, were recently questioned by studies failing to replicate them, forming a relative consensus according to which there is essentially no or very limited integrative (associative) processing under unconscious conditions [83][84][85][86].…”
Section: Processing Scene-object Associative Relationsmentioning
confidence: 99%
“…Theories such as unconscious inference can be traced back to Ibn al‐Haytham centuries ago (Allik & Konstabel, 2005), while laboratory studies of unconscious processing were already reported in the 1800s (Peirce & Jastrow, 1884; Suslowa, 1863). The scope and limit of unconscious processing, however, are still debated to this day (Goldstein & Hassin, 2017; Hassin, 2013; Hesselmann & Moors, 2015; Hirschhorn et al, 2021; Kouider & Faivre, 2017; Mudrik et al, 2014; Mudrik & Deouell, 2022; Rothkirch et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas higher‐level integration requires some kind of comparison (i.e. judging the relationship between two or more elements), which has also been described as ‘relational processing’ (Hirschhorn et al, 2021; Zucker & Mudrik, 2019). Examples include the representation of the number ‘5’ formed by comparing ‘3’ and ‘2’, or the concept of similarity/difference formed by comparing two stimuli (e.g.…”
Section: Introductionmentioning
confidence: 99%